Pemetaan Muka Air Tanah dengan Menggunakan Metode IDW dan Kriging di PT Bukit Baiduri Energi (Blok Utara) Kabupaten Kutai Kartanegara - Ayub Artha Christ Tiyawarman; Nia Kurniadin; Romansah Wumu; A. Arifin Itsnani SM (Journal of Geomatics Engineering, Technology, and Science, 2024)
This research was motivated by the need for information regarding the direction of water level distribution in the research area. By collecting mining concession boundary data, topographic data, and drilling data, it is necessary to present information that is easy for the company to understand. The aim of this research is to determine the accuracy of the IDW and Kriging methods in mapping groundwater levels. Primary groundwater level data collected using the systematic random sampling method was used to create an interpolation model. The accuracy of the interpolation model produced by the IDW and Kriging methods is known by observing the root mean square error (RMSE) parameters and validation tests. The best RMSE of the IDW method with five modeling experiments using 5 varying power (p) values. Meanwhile, the Kriging method uses Simple Kriging and Ordinary Kriging. The interpolation model for each method is then compared to find out which method has the best accuracy. Based on the results achieved, the best interpolation model using the IDW method was obtained using power (p) with a value of 5. The RMSE produced in this model was 10.14 with a validity of 49.01%. The best interpolation model using the Kriging method is obtained through the Ordinary Kriging variant. The RMSE produced by Ordinary Kriging is 8.61 with a validity of 38.21%. The research results show that the Kriging method is more accurate than the IDW method. The RMSE produced by the Kriging method has a lower value and higher validity.